Professionalism - Gallant, Shirley; Howe, Carol Anne; Wheaton, Donna (Operating Room Nurses Association of Canada Journal, 1994)
The Shorter Oxford English Dictionary deﬁnes professionalism as: 1. professional quality, character, method or conduct; the stamp of a particular profession. 2. the position of a professional as distinct from an amateur; the class of professionals 1884. Sec. 63-7-103 of The Tennessee Nurse Practice Act now states that the practice of professional nursing means, “the performance for compensation of any act requiring substantial specialized judgement and skill as the basis for application of the nursing process, in